Pengaruh Lingkungan Teman Sebaya, Dukungan Dosen, Fasilitas Kampus, dan Kedisplinan Diri terhadap Motivasi Berprestasi Mahasiswa Fakultas Bisnis dan Informatika: The Influence of Peer Environment, Lecturer Support, Campus Facilities, and Self-Discipline on Student Achievement Motivation in the Faculty of Business and Informatics - Ramadhani, Rahma; Mawaddah, Cintia Ayu; Haq, Muhammad Achiril (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The development of digital technology and global competition demands that students not only graduate but also have strong achievement motivation to compete in the world of work. This study aims to analyze the influence of peer environment, lecturer support, campus facilities, and self-discipline on students' achievement motivation in the Faculty of Business and Informatics. A quantitative approach was used by involving active students in the regular program who met the research criteria and were willing to complete a questionnaire. Data were analyzed using variance-based structural modeling in SmartPLS to identify relationships among variables. The results showed that peer environment, lecturer support, and self-discipline had a positive and significant effect on achievement motivation, whereas campus facilities did not. Self-discipline was the most dominant factor in increasing achievement motivation, followed by lecturer support and peer environment. These findings emphasize the importance of strengthening disciplined character, improving the quality of academic interactions, and creating a social environment that supports the learning process. This study contributes to efforts to develop strategies to increase student motivation and achievement. It can serve as a basis for policy research to improve the quality of education in the Faculty of Business and Informatics.